SELF DECLARE DALAM PROSES PENETAPAN SERTIFIKASI HALAL - Nahdhah Nahdhah; Iwan Riswandie (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2026)
This study aims to examine and analyze the regulatory framework of the self-declaration mechanism in the halal certification process and the adequacy of the normative basis for oversight by the Halal Product Assurance Organizing Agency (BPJPH) under Law Number 33 of 2014 concerning Halal Product Assurance. The research is prompted by several controversies, such as the